The role of bacterial cyclic di-adenosine monophosphate in the host immune response - Cheng, Xingqun; Ning, Jia; Xu, Xin; Zhou, Xuedong (Frontiers in Microbiology, 2022)
Cyclic di-adenosine monophosphate (c-di-AMP) is a second messenger which is widely used in signal transduction in bacteria and archaea. c-di-AMP plays an important role in the regulation of bacterial physiological activities, such as the cell cycle, cell wall stability, environmental stress response, and biofilm formation. Moreover, c-di-AMP produced by pathogens can be recognized by host cells for the activation of innate immune responses. It can induce type I interferon (IFN) response in a stimulator of interferon genes (STING)-dependent manner, activate the nuclear factor kappa B (NF-κB) pathway, inflammasome, and host autophagy, and promote the production and secretion of cytokines. In addition, c-di-AMP is capable of triggering a host mucosal immune response as a mucosal adjuvant. Therefore, c-di-AMP is now considered to be a new pathogen-associated molecular pattern in host immunity, and has become a promising target in bacterial/viral vaccine and drug research. In this review, we discussed the crosstalk between bacteria and host immunity mediated by c-di-AMP, and addressed the role of c-di-AMP as a mucosal adjuvant in boosting evoked immune responses of subunit vaccines. The potential application of c-di-AMP in immunomodulation and immunotherapy was also discussed in this review.